Perception of Antioquian speakers towards the normative Andean variety based on PRECAVES XXI - Muñoz-Builes, Diana Marcela (2025)
This paper has the aim to present the perception held by people from Antioquia regarding the Andean variety of Spanish within the framework of the Project for the study of beliefs and attitudes towards the varieties of Spanish in the 21st century (precaves xii). To achieve this, the responses from a sample of 108 Antioquian participants were analyzed, stratified by sex, age and educational level. The results suggest that for Antioquian speakers the most prestigious variety is their own, the Andean, which also has a high degree of exact identification. Regarding direct and indirect evaluations, the Andean variety is perceived in positive terms, highlighting its closeness and clarity, spoken by educated and cultured people, in a beautiful and familiar country with a quite interesting culture. These attitudes and beliefs are analyzed transversally due to the social distribution of the participants using direct and indirect assessments.